Restarting the future how to fix the intangible economy - Haskel, Jonathan (Princeton, New Jersey Princeton University Press., 2022)
"Restarting the Future argues that the big economic challenges facing the world are the result of our failure to deal with the implications of an economy dependent on knowledge, ideas and relationships. It examines why making this transition is so hard, and looks at ways forward in the fields of public policy, business and finance. The troubling state of rich-world economies (low productivity growth, high inequality, populist instability, climate crisis) is significantly the result of the troubled and incomplete shift to a new type of economy - specifically, the move from an economy dependent on tangible capital to one dependent on intangible capital. At the heart of the problem is a significant slowdown in the pace of intangible investment since the financial crisis. (There were some early signs of this at the time the authors were writing their previous book, Capitalism without Capital, but new data now makes the severity and persistence of this slowdown clear.) This slowdown has happened because we lack the right institutions and strategies to encourage intangible investment and channel it effectively. What is more, there are significant groups with an interest in stopping these new institutions emerging. Contrary to the dominant narrative that focuses on the tension between a successful, future-facing "elite" and a mass of low-status "left-behinds", the authors argue that many of the people and organisations with an interest in holding back the future are affluent and high-status, including affluent retirees, established financial institutions and graduate knowledge workers. Haskel & Westlake survey attempts to fix these institutional problems, explaining how they work in the context of the intangible economy, and what the upside to solving them might be. They describe interesting and topical policy experiments and business strategies (such as Preston's Local Economic Strategy, or topical new business models like WeWork and CloudKitchens) and set them in a novel economic context. (Specifically, these sections look at city policy, business finance and investment, public investment, competition policy, monetary policy, mitigating climate change and business strategies for tangible-based firms. The authors close the book with a political programme for how to get over the teething troubles of the new economy"
Keywords: Intangible property--Economic aspects